Exploring written and spoken english language accuracy via digital storytelling / Nor Nadia Raslee - Raslee, Nor Nadia (Universiti Teknologi MARA, Kedah, 2020)
This study was an exploration of Digital Storytelling as a pedagogical tool in the undergraduates' ESL classroom to measure ESL learners' written and spoken English language accuracy. Digital Storytelling has five main stages that allow students to be tested in various soft skills and language skills, specifically, writing and speaking. Over the duration of ten weeks, Digital Storytelling was developed, and data was collected at the end of this period. Seventeen reflective journals and 38 vlogs from 55 participants were analysed for errors based on the measurement for language accuracy which were the T-unit and C-unit. The findings indicated that both written and spoken language accuracy were not impactful following the completion of Digital Storytelling. 13 language accuracy errors were discovered in participants' written language, while, spoken accuracy revealed 12 errors. Accuracy was highly affected by subject-verb agreement errors, vocabulary errors, first language interference, and verb forms. These findings affirmed other literature which found that ESL learners lack mastery in grammar, tenses, sentence structure, and vocabulary, among many others. Conclusively, the literature indicated that the influence of the first language, learners' inhibition, lack of exposure and negative attitudes were among the causes of poor English language accuracy.